2021
DOI: 10.3390/su13020466
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Waste Flow in Industrial Symbiosis System at City-Region Level: A Case Study of Jinchang, China

Abstract: Waste is increasingly used as a renewable resource. Industrial symbiosis is an innovative concept for more efficient use of waste streams within industrial complexes, with the aim of reducing the overall environmental impact of the complex. Industrial symbiosis plays a more important role in promoting green economic growth and building low-carbon cities. Based on the ecological theoretical framework, combined with Waste Flow Analysis (WFA), the material flow analysis (MFA) and production matrix methods were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Food‐Web Theory and Supply Chain Theory as supporting theories can contribute to this point. The integration of social and technical systems can incorporate IS in the city and regional‐level metabolisms (Chaker et al, 2021). Socio‐Technical Systems Theory and Material Metabolism Theory are theories with the potential to simulate the waste stream metabolism (Lu et al, 2021). Social aspects dynamics aim at network consolidation by stakeholder engagement and discuss the local success or failure of IS (Morales & Diemer, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Food‐Web Theory and Supply Chain Theory as supporting theories can contribute to this point. The integration of social and technical systems can incorporate IS in the city and regional‐level metabolisms (Chaker et al, 2021). Socio‐Technical Systems Theory and Material Metabolism Theory are theories with the potential to simulate the waste stream metabolism (Lu et al, 2021). Social aspects dynamics aim at network consolidation by stakeholder engagement and discuss the local success or failure of IS (Morales & Diemer, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hein et al (2017) similarly mentioned that industrial symbiosis enables traditionally independent industries to gain a competitive advantage by way of exchange and cooperation in the production of raw materials, energy, and by-products and analyzed the case of symbiosis of a steam network of waste incinerators in France with the help of the case of symbiosis of a waste incinerator, which was analyzed at the microlevel and found that the government sector can obtain an improvement of its environmental performance in the context of industrial symbiosis. Lu et al (2021) pointed out that China's waste recycling system is characterized by a low level of waste recycling, abundant waste resources, and low efficiency of waste resource utilization and that the closer the interindustry linkage and the better the symbiosis system, the higher the waste recycling efficiency. Some scholars have also studied whether the development of industrial symbiosis can improve the economic situation of industries from the perspective of economic efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, to better realize the circular flow of ISW generation-transfer-management-reuse, different industries need to achieve effective aggregation, and such ISW technology is called ‘industrial symbiosis’ (Sellitto et al, 2021). ‘Industrial symbiosis’ technology can effectively enhance ISW management technology and reduce ISW management costs, thus promoting ISW recycling while realizing the green circular economy development (Lu et al, 2021). The models constructed by scholars have not been widely considered technology innovation in ISW management, although ISW management technology in industrial enterprises is an important principle.…”
Section: Introductionmentioning
confidence: 99%